Predictors of overload in parents of children with neuromuscular diseases - Rodríguez, A. A.; García, M.; Martínez, Oscar; López-Paz, J. F.; García, I.; Pérez-Nuñez, P.; Amayra, I. (Frontiers in Neurology, 2024)
Introduction Parents of children with neuromuscular diseases experience multiple difficulties in their daily lives that affect their physical and psychological health. The risk factors for these health issues have not been sufficiently investigated. Therefore, the aim of this study was to analyze the potential predictors of overload in these parents, including QoL, somatic symptomatology, life satisfaction, psychological adjustment and certain sociodemographic variables. Methods A cross-sectional research study was conducted among parents who are caregivers for children with NMD in Spain. A convenience sample of 110 parents who were contacted by associations and hospitals was used. Variables were evaluated using the sociodemographic questionnaire, CarerQol-7D, PHQ-15, Barthel Index, Psychological Adaptation Scale, Zarit Overload Scale and Satisfaction with Life Scale. Results One of the most relevant findings of the present study is the identification of 3 overload groups (mild to moderate, moderate to severe, and severe overload) based on life satisfaction and somatic symptom scores within the predictive model of the discriminate analysis. Wilk’s lambda of the discriminant function was 0.568, χ2 (2, n = 55) = 8.815, p < 0.001. Discussion This study presents a model that reveals the influence of unemployment, having a child with a severe level of dependency, the presence of somatic symptomatology and life satisfaction on caregiver overload. Likewise, the caregiver’s self-esteem could be a protective factor against overload.